The Impact of Trade Openness, Green Bond Issuance, and Global Shocks on Renewable Energy Consumption in Southeast and South Asia: A Panel Data Analysis - Hafidzoh, Qonitatun; Wulandari, Permata (Green Publisher Indonesia, 2025)
The urgent need for energy transition and escalating climate crisis have placed renewable energy at the forefront of policy and investment agendas in developing countries. This study investigates the impact of trade openness, green bond issuance, governance quality, and global shocks on renewable energy consumption in South and Southeast Asia (2016–2022), using quarterly panel data and FMOLS estimation. Results show that trade openness and governance quality significantly promote renewable energy adoption, while green bonds are not significant under normal conditions but become effective during global crises. These findings highlight the need for policies that not only support green energy under stable conditions but also ensure resilience against global disruptions, with green finance serving as a crucial stabilizing tool.